Inhaled corticosteroids and incidence of pneumonia in chronic obstructive pulmonary disease (COPD) patients: A review - Yuda Anzas Mara; I Dewa Putu Pramantara S; Zullies Ikawati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Chronic obstructive pulmonary disease (COPD) is a worldwide respiratory disease that causes significant morbidity and mortality. The primary emphasis in managing COPD is on symptom control and preventing exacerbations. However, there has been ongoing discussion surrounding the safety of inhaled corticosteroids (ICS). This narrative review aimed to examine ICS influence on pneumonia in patients with COPD by consolidating findings from randomized controlled trials and observational studies. The data indicated that the utilization of ICS may be linked to a heightened susceptibility to pneumonia, with varying levels of risk reported across different ICS drugs. Regimens containing fluticasone were found to exhibit an increased susceptibility to pneumonia. The presence of a dose-dependent correlation between ICS and the incidence of pneumonia is apparent. Further investigation is necessary to clarify the fundamental principles and enhance treatment recommendations to maximize the management of COPD while minimizing the incidences of pneumonia associated with ICS.